2006
DOI: 10.1007/s11240-006-9144-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term subculture randomly affects morphology and subsequent maturation of early somatic embryos in maritime pine

Abstract: Somatic embryogenesis is affected by highly variable maturation yields in Pinus pinaster. Origins of this variability were investigated by testing effects of spatial and temporal division of initial embryogenic tissue into independently cultivated pieces. One embryogenic cell-line was proliferated to obtain six embryonal-suspensor masses (ESM) treated as six sub-lines within a single dish. After proliferation to reach 2, 4 and 8 dishes (12, 24, 48 ESM), the 48 ESM (six sub-lines) were maintained by weekly subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…EM culture subdivision during proliferation at both spatial (Petri dish) and temporal levels (subline) did not affect the se production capacity of P. pinaster EM lines (Breton et al 2006), indicating that environmental conditions were homogeneous and standardized. In contrast, EM growth was strongly impacted by cell density on the filter paper (optimal in the range of 50-100 mg fresh mass for most embryogenic lines) and medium formulation.…”
Section: Multiplication Of Em and Progressive Reduction In Somatic Emmentioning
confidence: 94%
See 2 more Smart Citations
“…EM culture subdivision during proliferation at both spatial (Petri dish) and temporal levels (subline) did not affect the se production capacity of P. pinaster EM lines (Breton et al 2006), indicating that environmental conditions were homogeneous and standardized. In contrast, EM growth was strongly impacted by cell density on the filter paper (optimal in the range of 50-100 mg fresh mass for most embryogenic lines) and medium formulation.…”
Section: Multiplication Of Em and Progressive Reduction In Somatic Emmentioning
confidence: 94%
“…Considering the ratio of fully developed cotyledonary se to precotyledonary and abnormal se at various sampling times during proliferation, Breton et al (2006) showed that the maturation of se was qualitatively unchanged, but that it quantitatively and progressively reduced as the number of consecutive subcultures and, hence, the chronological age of the cultures increased.…”
Section: Multiplication Of Em and Progressive Reduction In Somatic Emmentioning
confidence: 99%
See 1 more Smart Citation
“…Since elite genotype www.intechopen.com selection is on the basis of both in vitro and ex vitro evaluations, the process from somatic embryo initiation to mass seedling production can be long. A consequence of this extended time period is that embryogenicity may diminish or even be irrevocably lost in a few weeks or months (Breton et al, 2006). A way around this problem is to cryopreserve tissues while they are at their peak productivity, shortly after embryogenic tissue induction and when enough tissue is available (Kong and Aderkas, 2011).…”
Section: Regeneration Of Plants After Cryopreservationmentioning
confidence: 99%
“…Maybe the main reason of this has been the difficulty to make transgenic crop plants, and the limited number of full sequenced genomes compared to microorganisms until now. Although at present, it is possible to transform almost all crop plants [3], including some trees like poplar [4] and pine [5,6], and the number of full sequenced genomes of plant species is highly increased in the last years; thanks to next generation sequencing techniques [7]. In the present moment, we have enough technology to attend the protein engineering in plants.…”
mentioning
confidence: 99%